2010
DOI: 10.1111/j.1365-2966.2010.16872.x
|View full text |Cite
|
Sign up to set email alerts
|

Feedback and recycled wind accretion: assembling the z= 0 galaxy mass function

Abstract: We analyse cosmological hydrodynamic simulations that include theoretically and observationally motivated prescriptions for galactic outflows. If these simulated winds accurately represent winds in the real Universe, then material previously ejected in winds provides the dominant source of gas infall for new star formation at redshifts z < 1. This recycled wind accretion, or wind mode, provides a third physically distinct accretion channel in addition to the ‘hot’ and ‘cold’ modes emphasized in recent theoreti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
727
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 491 publications
(786 citation statements)
references
References 101 publications
(151 reference statements)
55
727
4
Order By: Relevance
“…We analyze highresolution simulations of 20 spiral and dwarf galaxies that span 2.5 orders of magnitudes in virial mass, all simulated with the same physics and comparable numerical resolution. Our work improves on previous particle tracking analyses that have focused either on low-resolution (non-zoom) simulations of many galaxies (Oppenheimer et al 2010) or on a few simulations of similar-mass galaxies (Brook et al 2012a;Übler et al 2014;Woods et al 2014) and complements non-particletracking studies of galactic winds (Muratov et al 2015).…”
Section: The Analysis Of Outflows Presented Herementioning
confidence: 63%
See 3 more Smart Citations
“…We analyze highresolution simulations of 20 spiral and dwarf galaxies that span 2.5 orders of magnitudes in virial mass, all simulated with the same physics and comparable numerical resolution. Our work improves on previous particle tracking analyses that have focused either on low-resolution (non-zoom) simulations of many galaxies (Oppenheimer et al 2010) or on a few simulations of similar-mass galaxies (Brook et al 2012a;Übler et al 2014;Woods et al 2014) and complements non-particletracking studies of galactic winds (Muratov et al 2015).…”
Section: The Analysis Of Outflows Presented Herementioning
confidence: 63%
“…Cosmological simulations predict that the recycling time for momentumdriven wind scales roughly inversely with the halo mass for moderate-sized star-forming galaxies (Oppenheimer & Davé 2008;Oppenheimer et al 2010), and some semianalytic models have found that similar scalings are best able to reproduce various observations, such as the stellar mass function (Henriques et al 2013). Here we directly track the recycling time in our simulations as a function of halo mass.…”
Section: Wind Recyclingmentioning
confidence: 97%
See 2 more Smart Citations
“…Bouché et al, 2010;Dutton et al, 2010;Lagos et al, 2011;Davé et al, 2012). In galaxy formation theory, the baryonic gas fraction is set by a balance between gas accretion from the intergalactic medium (IGM), and the removal of gas by star formation and galactic outflows (with small perturbations from stellar mass loss and recycled gas outflows Oppenheimer et al, 2010). At higher redshifts, the baryonic inflow rate, which scales strongly with redshift (e.g.…”
Section: Molecular Gas Fractionsmentioning
confidence: 99%